Transcriptome sequencing reveals the key genes associated with hair follicle development in Qianhua Mutton Merino - Qin, Zhiyun; Sun, Xinming; Sun, Limin; Yu, Meng; Jiang, Huaizhi (Frontiers in Veterinary Science, 2025)
BackgroundThe aim is to compare the morphological changes and gene expression profiles of hair follicles in newborn and one-year-old Qianhua Mutton Merino sheep, explore the changes in gene expression and related regulatory pathways during the process from incomplete development to full development of skin hair follicles, and identify the key genes influencing hair follicle development and maturation. This study holds significant theoretical importance for revealing the molecular regulatory mechanism of hair follicle development in Qianhua Mutton Merino sheep.MethodsA total of five newborn (1-day-old) and five yearling (12-month-old) Qianhua Mutton Merino sheep were selected for this study. Skin tissue samples were collected for histological analysis using HE staining. Transcriptome sequencing was performed on the Illumina NovaSeq 6000 platform, and differentially expressed gene (DEG) analysis was conducted using the R package degeR. GO and KEGG pathway enrichment analyses were performed on the DEGs to identify genes associated with hair follicle development. Ten DEGs were randomly selected for the validation of the transcriptome sequencing results using realtime quantitative PCR. The KRT27 gene was further validated through immuno-histochemistry and quantitative PCR.ResultsThe results from HE staining indicated that with an increase in the age of the Qianhua Mutton Merino sheep, the density of both primary and secondary hair follicles significantly decreased (p < 0.05), while the S/P ratio exhibited a remarkable increase (p < 0.05). The transcriptome sequencing results identified a total of 1,637 differentially expressed genes, of which 1,134 were upregulated and 503 were downregulated. GO and KEGG enrichment analyses of DEGs related to hair follicle development revealed that these genes were enriched in signaling pathways associated with hair follicle development, such as the PI3K-Akt, MAPK, and Estrogen signaling pathways. The results of real-time quantitative PCR were consistent with the transcriptome sequencing results. The KRT27 gene was expressed in the inner root sheath region of hair follicles, with a significant upregulation observed at 12 months of age (p < 0.05).ConclusionIn conclusion, this study identified the KRT27, IGF-2, FGF21, VEGF-D, KRT25, and KRT26 genes as important candidate genes in the development of hair follicles in Qianhua Mutton Merino sheep through transcriptome sequencing analysis, providing a theoretical basis for further revealing the molecular mechanisms underlying the formation of wool traits in Qianhua Mutton Merino sheep.